Chemical soil attributes after wheat cropping under nitrogen fertilization and inoculation with Azospirillum brasilense - Galindo, Fernando Shintate [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Buzetti, Salatiér [UNESP]; Santini, José Mateus Kondo [UNESP]; Bellotte, João Leonardo Miranda; Ludkiewicz, Mariana Gaioto Ziolkowski [UNESP]; Andreotti, Marcelo [UNESP]; Silva, Vinicius Martins [UNESP]; De Paula Garcia, Cássia Maria [UNESP] (Universidade Estadual de Londrina, 2017)
Azospirillum brasilense plays an important role in biological nitrogen fixation (BNF) in grasses. However, further studies are needed to define how much mineral N can be applied while simultaneously maintaining BNF contribution and maximizing crop yield and to determine the impact of these practices on soil fertility. Thus, we aimed to investigate the effect of inoculation with A. brasilense, in conjunction with varying N doses and sources in a Cerrado soil, on soil chemical attributes after two years of irrigated wheat production. The experiment was initiated in Selvíria - MS under no-tillage production in an Oxisol in 2014 and 2015. The experimental design was a randomized block design with four replications, and treatments were arranged in a 2 × 5 × 2 factorial arrangement as follows: two N sources (urea and Super N - urea with inhibitor of the enzyme urease NBPT (N - (n-butyl thiophosphoric triamide))), five N rates (0, 50, 100, 150 and 200 kg ha-1), and with or without seed inoculation with A. brasilense. The increase in N rates did not influence the chemical soil attributes. Super N acidified the soil more compared to urea. A. brasilense inoculation reduced the effect of soil acidification in intensive irrigated wheat cultivation; however, the base extraction was higher, resulting in a lower soil CEC after cultivation with inoculation. Therefore, the cultivation of wheat inoculated with A. brasilense was not harmful to soil fertility because it did not reduce the base saturation and organic matter contents of, P, K, Ca, Mg, and S.
Keywords: Biological nitrogen fixation; No-tillage system; Soil fertility; Triticum aestivum; Urease inhibitor